POLA PENDIDIKAN ISLAM PADA MASA DINASTI SYAFAWI - Samsul Bahri (Tarbawi, 2021)
The aim of this research is to understand the pattern of education during the Safavid dynasty in Persia, as well as to try to identify elements that could possibly be reconstructed from the golden age of Islam, for Islamic education in Indonesia today. The research method used in this study is literature review. The results of the research show that during the rule of the Safavid dynasty in Persia, Islamic education played a significant role in shaping society and political power. The Safavid kings established an education system based on Shia Islamic teachings, with main centers in Qom, Isfahan, and Najaf. They founded madrasahs to spread religious teachings, literature, and other Islamic knowledge. For Islamic education in Indonesia today, it is important to focus on deep understanding, skills and character development, and the implementation of modern educational methods. By considering the principles of the golden age of Islam in the past, Islamic education in Indonesia can be improved to produce intelligent, morally upright generations capable of competing in the era of globalization.